High expression of CXCL13 predicts a favorable response to immunotherapy by upregulating CXCR5+CD8+ T-cell infiltration in gastric cancer - Xu, Shuning; Li, Danyang; Ning, Tao; Lu, Yao; Sun, Yansha; Bai, Hua; Qiao, Lei; Deng, Ting; Liu, Ying (Frontiers in Immunology, 2025)
IntroductionIdentifying predictive biomarkers for immune checkpoint inhibitor (ICI) treatment is critical for gastric cancer (GC) prognosis. C-X-C motif chemokine ligand 13(CXCL13) plays an important role in immune regulation by binding exclusively to its receptor CXCR5. However, its role, underlying mechanisms, and prognostic significance in ICI-treated GC patients remain controversial.MethodsThis study investigated the clinical significance of CXCL13 and its potential immunomodulatory function in GC patients. A total of 144 GC patients from two cohorts, who received a combination of chemotherapy and anti-PD-1 antibody, were analyzed. The expression of CXCL13 was assessed using immunohistochemistry (IHC) and enzyme-linked immunosorbent assay. Associations between CXCL13, CXCR5, CD8, and CD4 were assessed by IHC and immunofluorescence. Survival analysis was performed using the Kaplan–Meier method and Cox proportional hazards model. The treatment response to CXCL13 and anti-PD-1 antibody was investigated using a subcutaneous xenograft tumor mouse model.ResultsThe results suggested that patients with high CXCL13 expression had prolonged survival. High CXCL13 expression exhibited increased infiltration of CXCR5+CD8+ T cells and was associated with better outcomes. The combined assessment of CXCL13, CXCR5, and CD8+ T cells served as an independent predictor of prognosis. Additionally, CXCR5 and CD8+ T cells were enriched in tertiary lymphoid structures (TLSs), which conferred a prognostic benefit in the presence of high CXCL13 expression. CXCL13, in combination with anti-PD-1 therapy, retarded tumor growth in vivo, resulting in increased infiltration of CXCR5+CD8+ T cells.DiscussionThis study identified CXCL13 as a prognostic factor in GC patients receiving ICI therapy, emphasizing its critical role in the antitumor microenvironment via CXCR5+CD8+ T cells.